A polymorphism in the MTHFD1 gene increases a mother's risk of having an unexplained second trimester pregnancy loss. - MOLLOY, ANNE MARIE; SCOTT, JOHN MARTIN (Oxford University Press, 2005)
Low maternal folate or vitamin B12 status has been implicated in numerous pregnancy complications including spontaneous abortion. The primary aim of this study was to test a polymorphism within the trifunctional folate enzyme MTHFD1 (5,10-methylenetetrahydrofolate dehydrogenase, 5,10-methenyltetrahydrofolate cyclohydrolase, 10-formyltetrahydrofolate synthetase) for an association with a mother?s risk of having an unexplained second trimester pregnancy loss. We genotyped 125 women who had at least one unexplained spontaneous abortion or intrauterine fetal death between 13 and 26 weeks gestation and 625 control women with no history of prior pregnancy loss. Our study is the first to identify an association between the MTHFD1 1958GA (R653Q) polymorphism and the maternal risk of having an unexplained second trimester pregnancy loss. Women who are MTHFD1 1958AA homozygous have a 1.64-fold increased risk of having an unexplained second trimester loss compared to women who are MTHFD1 1958AG or 1958GG [OR 1.64 (1.05?2.57), P = 0.03]. It has been reported that polymorphisms in 5,10-methylenetetrahydrofolate reductase (MTHFR), 677CT (A222V), transcobalamin II (TCII), 776CG (P259R), are associated with pregnancy loss. Both variants were tested in this study. Neither showed evidence of significantly affecting the maternal risk of having a second trimester pregnancy loss. In conclusion, the MTHFD1 1958AA genotype may be an important maternal risk factor to consider during pregnancy.
PUBLISHED
Keywords: abortion fetal death second trimester/spontaneous unexplained